Child Marriage in Indonesia: Sexual Violence or Not? - Inna Fauzi; Any Ismayawati (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2022)
Child marriage in Indonesia presents a progressive article as stated in Article 4 of Law Number 12 of 2022 concerning the crime of sexual violence. This is a problem that is quite complicated for the Indonesian people because child marriage creates new problems because it contains elements of punishment. In this regard, this paper aims to examine how the interpretation of the article on the punishment of children is carried out, how to implement the elements of punishment for child marriage as stipulated in the Act on the Crime of Sexual Violence and how to review Islamic law on the article on the punishment of child marriage. The results of the study show that the Article policy with certain threats for perpetrators of mental sexual violence through child marriage is carried out by giving criminal sanctions. the implementation of punishment for the perpetrators involved in the occurrence of child marriages with coercion is the use of criminal sanctions. while the review of Islamic law on the article on criminalizing child marriage should be measured more deeply using the right of ijbar and ikrah as they should because both have different positions and meanings.